Investigation of spatial relationships in the gravity zone of Paks and Kalocsa - Káposzta, József; Lőrinc, Balázs; Urbánné Malomsoki, Mónika (Studia Mundi – Economica, 2020)
The current and planned enhancements - which are taking place at Paks and its agglomeration - are important factors either for the local society, the economy or the infrastructure. The area developments which own a high priority nationwide, could be understandable and transparent by the investigation of the mentioned sub-systems. In the case of the district of Kalocsa – as part of the „gravitational-zone” – we can formulate that the Danube circumscribe Paks from Kalocsa, which in the flow of labour and other goods - inter alia - can appear as a disadvantage in terms of the mobility. The Danube-bridge which is under construction, could be the first step in the conjuncture the endogeneous source of these two economical area, which may generate an economic growth.